Ethical meaning and academic responsibility in Generative Artificial Intelligence policy in higher education - Fransiskus Xaverius Sabu; Taufik Asmiyanto (Berkala Ilmu Perpustakaan dan Informasi, 2026)
Introduction. This study interprets policy texts on Generative AI in higher education through an ethical and existential lens, using a hermeneutic-phenomenological approach to explore how they cultivate critical awareness and ethical responsibility in AI use for learning. Research Methods. The research uses Paul Ricoeur’s hermeneutic phenomenological approach to analyze GenAI policy texts in higher education, revealing how the constructs that shape ethically oriented AI discourse. Data Analysis. The data analyzed consist of policy texts on the use of GenAI in higher education. The analyses were conducted through thematic coding to identify the main topics, followed by hermeneutic interpretation to reveal the deeper meaning constructed by the texts within the context of ethics and education. Result. The analysis revealed four key findings: the interpretation of GenAI as a learning aid, the emphasis on ethics and academic integrity, the tension between regulation and institutional autonomy, and the transformation of the lecturer-student relationship. Collectively, these findings indicate that GenAI policies cultivate a new awareness of the ethical use of technology within higher education institutions. Conclusion. The GenAI policy is not merely a technical guide but a discourse that shapes the academic community’s ethical awareness, fostering a critical and responsible use through a hermeneutic-phenomenologicallens.